Interpreting a Classic : Demosthenes and His Ancient Commentators - Gibson, Craig A., 1968- (Book collections on Project MUSE., 2002)
Gibson tells the story of how one group of ancient scholars helped their readers understand Demosthenes writings. This book translates and offers explanatory notes on all the fragments of ancient philological & historical commentaries on Demosthenes.